The Effects of Antivirals for Human Immunodeficiency Virus Treatment on Renal Functions - Mehmet ÇABALAK; Tayibe BAL; Faruk Hilmi TURGUT (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2022)
Objective: Turkey is among the countries with a low incidence of the human immunodeficiency virus (HIV) infections. When HIV cases are decreasing worldwide, our country is among the countries where the number of patients is rapidly increasing. Tenofovir disoproxil fumarate (TDF), tenofovir alafenamide (TAF), and abacavir are the drugs used for HIV treatment in Turkey. The estimated glomerular filtration rate (eGFR) is widely used as a kidney function indicator. This study aimed to investigate the effects of TDF and TAF-based regimens on renal function. Materials and Methods: During the study period, 104 patients who are HIV-positive underwent treatment with an antiretroviral therapy (ART) regimen, of whom 60 fulfilled the inclusion criteria and were included in the study. This study retrospectively examined the effects of TAF and TDF-based regimens on eGFR and other routine parameters. Results: Patients receiving TDF-based regimens revealed significantly increased serum creatinine and decreased eGFR levels compared to pre-treatment levels. Conversely, patients receiving a TAF-based regimen did not show significant changes in eGFR or serum creatinine levels. Conclusion: Our data indicate that eGFR levels decrease with a TDF-based regimen. Thus, with TDF as a component of the ART regimen, eGFR levels should be carefully monitored. TDF-free regimens should be used in patients who are predicted to have impaired renal function and those with renal function changes during treatment.